Design of a Motor Vehicle Tax Payment Management Information System with the Integration of a Lucky Draw Feature Based on UI/UX Figma - Ahmad Akbar; Heri Kurniawan; Fachrid Wadly; Mhd Rohid Alfarizi (Journal of Information Technology, computer science and Electrical Engineering, 2025)
Motor vehicle tax payment is a civic obligation; however, the level of taxpayer compliance remains relatively low due to limited information, insufficient motivation, and suboptimal utilization of digital services. This study aims to design a Motor Vehicle Tax Payment Management Information System integrated with a Lucky Draw feature as a gamification element to increase taxpayer interest and engagement. The design process employs a User-Centered Design (UCD) approach and utilizes Figma to produce a UI/UX design that is easy to understand and aligned with user needs.The research output is a visual prototype consisting of a homepage, registration form, admin dashboard, Lucky Draw spin feature, and reporting module. The design is evaluated based on usability, navigation, clarity of information, and visual consistency. The integration of the Lucky Draw feature provides additional motivation for taxpayers to fulfill their tax obligations in a timely manner. This study contributes a modern, user-oriented digital solution design that has the potential to enhance the effectiveness of tax services and improve taxpayer compliance.`